Utilization of Digital Technology-Based Marketing For the Development of Micro, Small and Medium Enterprises - Basri, Muh. Arfah; Siradjuddin, Siradjuddin; Sudirman, Sudirman (Economics, Business, Accounting & Society Review, 2023)
This study examines the importance of digital technology-based marketing as a strategy to develop Micro, Small and Medium Enterprises (MSME). The method used was the study of literature. The advancement of information technology is growing. Some MSME activities use information technology to launch their business. The increasing number of competitors is a challenge for business owners who are unable to innovate to improve the current competitive situation. Digital marketing is widely chosen as a strategy as business improvement because of its low cost and effectiveness. Utilizing social media in marketing strategies has the potential to help MSME business actors market their products. Micro, Small and Medium Enterprises must be literate in information technology in order to make it easier to market their products to remote areas